Ikiru [videorecording (DVD)] - Kurosawa, Akira, 1910-1998; Shimura, Takashi, 1905-1982; Odagiri, Miki; Kaneko, Nobuo, 1923-1995; Prince, Stephen, 1955-2020-; Tolstoy, Leo, graf, 1828-1910 (Criterion collection, 2015)
A young Japanese businessman dying of cancer wants to give something back to society before his death, so he decides to build a playground for children.